Legal Protection for Notaries in Related Criminal Justice Proceedings in the Making of Deeds - Ripandi Ripandi; Surastini Fitriasih (Universitas Muhammadiyah Sumatera Utara, 2022)
The purpose of writing was to find out about legal protection for Notaries in the implementation of criminal justice processes related to deeds that have been made by Notaries. The research method used was normative juridical, which is conducting an assessment based on the provisions of the applicable laws and regulations. The result of the study was that legal protection for Notaries was primarily provided in Article 66 of the UUJN with the establishment of the Notary Honorary Council (MKN), the aim of which was to provide maximum legal contribution to Notaries in carrying out their duties, and to receive protection as a member of the Indonesian Notary Association (INI). The obstacle in its implementation was that the implementing regulations for the UUJN have not yet been formed, causing there to be articles that provide multiple interpretations in their implementation. In addition, INI's role was still lacking in conducting outreach to the community